Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Section 10.4 - Adding, Subtracting, and Multiplying Radical Expressions - Exercise Set: 66



Work Step by Step

$(\sqrt{y}-3x)^{2}$ Evaluate this power using the formula for squaring a binomial. The formula is $(a-b)^{2}=a^{2}-2ab+b^{2}$. In this expression, $a=\sqrt{y}$ and $b=3x$ Substitute the known values in the formula and simplify: $(\sqrt{y}-3x)^{2}=(\sqrt{y})^{2}-2(3x)\sqrt{y}+(3x)^{2}=...$ $...=y-6x\sqrt{y}+9x^{2}=9x^{2}-6x\sqrt{y}+y$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.